The PSI as a Shared Good: How the Proliferation Security Initiative Both Challenges and Reinforces a Prevailingly Mare Liberum Regime. (2nd October 2018) - Perry, Timothy
Abstract : Since 2003, the Proliferation Security Initiative (PSI) has grown from a small collection of like-minded states into a widely accepted, and increasingly institutionalized, counterproliferation effort. However, while the PSI has evolved, the literature around it has stagnated—and disserves ongoing debate by adopting a framework that is both ahistorical and binary. Building on the author's 2007 paper, this article assesses the past 15 years' critiques, and argues that the PSI paradoxically reinforces our prevailingly mare liberum regime at the same time that it challenges established navigational freedoms such as the right of innocent passage.